Computational docking, molecular dynamics simulation and subsite structure analysis of a maltogenic amylase from Bacillus lehensis G1 provide insights into substrate and product specificity - Manas, N. H. A. (Elsevier Inc., 2016)
Maltogenic amylase (MAG1) from Bacillus lehensis G1 displayed the highest hydrolysis activity on β-cyclodextrin (β-CD) to produce maltose as a main product and exhibited high transglycosylation activity on malto-oligosaccharides with polymerization degree of three and above. These substrate and product specificities of MAG1 were elucidated from structural point of view in this study. A three-dimensional structure of MAG1 was constructed using homology modeling. Docking of β-CD and malto-oligosaccharides was then performed in the MAG1 active site. An aromatic platform in the active site was identified which is responsible in substrate recognition especially in determining the enzyme's preference toward β-CD. Molecular dynamics (MD) simulation showed MAG1 structure is most stable when docked with β-CD and least stable when docked with maltose. The docking analysis and MD simulation showed that the main subsites for substrate stabilization in the active site are -2, -1, +1 and +2. A bulky residue, Trp359 at the +2 subsite was identified to cause steric interference to the bound linear malto-oligosaccharides thus prevented it to occupy subsite +3, which can only be reached by a highly bent glucose molecule such as β-CD. The resulted modes of binding from docking simulation show a good correlation with the experimentally determined hydrolysis pattern. The subsite structure generated from this study led to a possible mode of action that revealed how maltose was mainly produced during hydrolysis. Furthermore, maltose only occupies subsite +1 and +2, therefore could not be hydrolyzed or transglycosylated by the enzyme. This important knowledge has paved the way for a novel structure-based molecular design for modulation of its catalytic activities.